POSITIVES AND NEGATIVES OF PARTNERSHIP STRATEGY BETWEEN NURSERY AND PRIMARY SCHOOLS - PROVAZKOVA STOLINSKA, Dominika; Miroslav, JANU (Trends in education, 2015)
Through the article we would like to outline the contextuality of pre-primary and primary education in focus on the advantages and disadvantages and their implementation in educational activities at these school grades within one institution. If we perceive primary education as the beginning of compulsory education, then the undeniable importance of pre-primary education we can see as a purposeful preparation of the child for successful entry into the educational process. The intention of the article is to present a vision of follow up the curriculum of these two levels in confrontation with real levels of this issue in practice at nursery and primary schools. The reflexion of reality was determined by analyzing the opinions stratified selected from the sample of respondents.
Keywords: preprimary education; primary education; compulsory education; curriculum; research.